The Complementizers kad and jog ‘that’ in old and Contemporary Lithuanian - Jasionytė-Mikučionienė, Erika (Vilnius University Open Series, 2018)
[full article and abstract in Lithuanian; abstract in English]This paper focuses on the Lithuanian complementizers kad and jog (“that”), which so far have not received any in-depth analysis, except for some observations made by the authors of the Lithuanian Grammar (1976) or Artūras Judžentis (2009) and Axel Holvoet (2010; 2015). Adopting both synchronic and diachronic perspectives and by applying a corpus-driven methodology, the present study aims to investigate the semantic functional potential of kad and jog as well as their usage and the syntactic contexts that they appear in. The analyzed data set includes both written (i.e., fiction) language and some Old Lithuanian texts from the 16th century (namely, the Postilla by Jonas Bretkūnas (1591) and the Postilla by Mikalojus Daukša (1599)).The analysis shows that the complementizers under consideration are relatively frequent in the old Lithuanian writings, though the complementizer kad is only sporadically used in Jonas Bretkūnas’s Postilla. The conjunction kad in the Postilla by Mikalojus Daukša is most often used in different types of adverbial clauses, including time, purpose and conditional clauses. Jog, in its turn, functions as a complementizer that prototypically appears in propositional complement clauses (in both of the analyzed old texts). When, in the Daukša’s Postilla, the conjunction kad appears in complement clauses, it may take on both types (i.e., propositional as well as state-of-affairs) of complement clauses. In contemporary Lithuanian, kad has changed its functional profile and, like the complementizer jog, is most often associated with complementation strategies; i.e., it is found in propositional and state-of-affairs complement clauses. Besides, kad is more polyfunctional than jog: it can be found in insubordinate clauses and function as a discourse or an optative marker.